Experiment on the Effect of Pineapple Ecoenzyme on the Morphological Growth of Green Beans (Vigna radiata L.) as an Effort to Promote Environmentally Friendly Fertilization - Faudina Permatasari (Postgraduate, University of Mataram, 2025)
This study aims to analyze the effectiveness of pineapple peel waste-based ecoenzymes as liquid organic fertilizer on the height growth of mung beans (Vigna radiata L.). Ecoenzymes are the result of organic waste fermentation with carbon sources from sugar and water, produced through the activity of decomposing microbes. The compounds contained therein, such as enzymes, organic acids, and beneficial microorganisms, play an important role in increasing soil biological activity, improving soil structure, and accelerating the absorption of nutrients by plant roots. The research was conducted in a laboratory experiment using a three-main-treatment design, namely: control without fertilizer, application of pineapple ecoenzyme liquid organic fertilizer, and application of EM4 liquid organic fertilizer as a commercial comparison. Observations were made every two days during a 14-day period, focusing on the variable of plant height increase. The results showed that the pineapple ecoenzyme treatment significantly increased vegetative plant growth, with an average growth of 10.40 cm, higher than the control (6.20 cm) and close to the EM4 results (11.10 cm). These findings confirm that pineapple ecoenzyme has the potential to be an environmentally friendly liquid organic fertilizer alternative, which not only supports plant growth but also contributes to sustainable household organic waste management